Pengaruh asap rokok elektrik terhadap kekasaran komposit nanohibrid dan bulkfill (Laporan Penelitian) - Immanuel Leon; Tien Suwartini (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Background: Nanohybrid and nanohybrid bulkfill are two type of modified composites that were made to have low shrinkage level. These composites can have increased surface roughness after electric cigarette smoke exposure. Objective: To determine the difference of electric cigarette smoke exposure effect on surface roughness of nanohybrid and nanohybrid bulkfill composite. Method: 14 samples of nanohybrid and nanohybrid bulkfill composite were exposed to electric cigarette smoke for 7 days with 20 cycles of 10 blows for 4 second with 20 second pause for each blows, surface roughness for each samples were measured on day 0, day 3, day 5 and day 7. Samples were incubated for ± 24 hours with a temperature of 37°C. Result: Average surface roughness increase of nanohybrid bulkfill is higher compared to nanohybrid on every measurements. Mann-Whitney test showed there are no significant surface roughness difference between nanohybrid and nanohybrid composite on every measurements. Conclusion: Average surface roughness increase of nanohybrid bulkfill is higher than nanohybrid composite. There was no significant difference of surface roughness between the two group of nanohybrid and nanohybrid bulkfill composite.